Hepatitis B virus relapse rates in chronic hepatitis B patients who discontinue either entecavir or tenofovir. Issue 2 (28th November 2018) - Kuo, Ming‐Te; Hu, Tsung‐Hui; Hung, Chao‐Hung; Wang, Jing‐Houng; Lu, Sheng‐Nan; Tsai, Kai‐Lung; Chen, Chien‐Hung
Summary: Background: Entecavir (ETV) and tenofovir disoproxil fumarate (TDF) are first‐line long‐term monotherapy for treatment of chronic hepatitis B (CHB) infection. High virological relapse rates are found after cessation of either ETV or TDF in CHB patients. Aim: To compare hepatitis B virus (HBV) relapse rates in CHB patients without cirrhosis who discontinued ETV or TDF. Methods: A retrospective‐prospective study was conducted in 342 CHB patients (108 hepatitis B e antigen (HBeAg)‐positive and 234 HBeAg‐negative) who received ETV and 165 (46 HBeAg‐positive, 119 HBeAg‐negative) who received TDF were recruited. All patients had post‐treatment follow‐up for at least 6 months. All fulfilled the stopping criteria of the Asia‐Pacific Association for the Study of the Liver of 2012. Results: Patients who discontinued TDF had significantly higher rates and earlier times of virological and clinical relapse than those who discontinued ETV. This was also seen in propensity score (PS)‐matched HBeAg‐positive and HBeAg‐negative patients. Multivariate analysis showed that being in the TDF group was an independent factor for virological and clinical relapse in all patients and PS‐matched HBeAg‐positive and HBeAg‐negative patients. The rate of off‐therapy HBsAg loss was comparable between the ETV and TDF groups after 2‐3 years follow‐up. Clinical relapse tended to be more severe in the TDF group compared with the ETV group. Conclusion: HBV relapse occurs sooner and is more severe after cessation of TDF than after cessation of ETV. Abstract : LINKED CONTENT This article is linked to Huang et al and Chen papers. To view this article visit https://doi.org/10.1111/apt.15150 and https://doi.org/10.1111/apt.15183 .